Trypanosome infections and other factors influencing PCV in livestock - D'Ieteren, G.D.M.; Awuome, K.; Bokovi, K.; Chema, S.; Colardelle, C.; Coulibaly, L.; Defly, A.; Feron, A.; Grundler, G.; Handlos, Michael; Hecker, P.; Itty, P.; et al. (ILCA/ILRAD, 1988)
Reviews some of the important factors influencing PCV value in livestock in six network sites. Includes data on the effect of no. of months with trypanosome parasitaemia on PCV in Djallonke sheep, pre-aand pos-partum on ewe PCV during lactation, on PCV of cattle, on PCV of N'Dama cattle; and PCV pre-weaning of male & female progens.